确定重载大模数齿轮深层渗碳深度的方法比较 - 李光瑾; 任颂赞; 滕鲁湘; 陈德华; 哈胜男; 祝兵寿; 蒋勇刚; 杨亚文; 王洪 (Jixie chuandong)
A variety methods of determining the depth of deep case carburizing of heavy-duty gear are compared,the variation of carburized depth requirement of heavy-duty gear in recent years are listed.The quench stress test of the carburizing samples with different diameter and the specimen with teeth shape are carried out.On the basis of compressing the depth redundancy of the existing deep carburized layer and referring to the variation of carburized depth in recent years,we can make great efforts to attribute lean process of carburized depth,appropriate reducing the depth,and on condition of ensuring gear load capacity,make deep carburizing process to a processing technology of energy conservation and emission reduction and clean efficient.